(untitled) (Journal of Philosophy Culture and Political Science, 2024)
Abstract: The article is devoted to the cultural analysis of the work of Kazakh artists in the first decade after the collapse of the Soviet Union. The last ten years of the XX cen. were a turning point in the culture of Kazakhstan. A content analysis of the works of domestic researchers related to the Kazakh Fine Arts of this period was carried out, current topics in the work of artists were analyzed. It was revealed that in this area of culture have been a positive trend towards preserving the spiritual identity of the nation, towards displaying its mentality and values. It is shown that the artists began to show more interest in the cultural identity of the nation and the search for new ways of depicting it. It is confirmed that this trend is a positive consequence of the state policy, which paid special attention to the Kazakh national culture in the first years of Independence. The article provides a structural and semantic analysis of the themes and ways of representing Kazakh painting and sculpture of the late XX cen., using the analogy method to determine their common features based on the national worldview and corresponding to national self-consciousness. In addition, a comparative analysis was made with trends in the world art of painting and sculpture, similarities and features were studied. The role of Fine Arts in the Kazakh spiritual culture during this period and its influence on further development is revealed. Keywords: national culture, Kazakh Fine Arts, tradition, painting, sculpture, national worldview.